The visible face of intention: why kinematics matters - Ansuini, Caterina; Cavallo, Andrea; Bertone, Cesare; Becchio, Cristina (Frontiers in Psychology, 2014)
A key component of social understanding is the ability to read intentions from movements. But how do we discern intentions in others’ actions? What kind of intention information is actually available in the features of others’ movements? Based on the assumption that intentions are hidden away in the other person’s mind, standard theories of social cognition have mainly focused on the contribution of higher-level processes. Here, we delineate an alternative approach to the problem of intention-from-movement understanding. We argue that intentions become ‘visible’ in the surface flow of agents’ motions. Consequently, the ability to understand others’ intentions cannot be divorced from the capability to detect essential kinematics. This hypothesis has far reaching implications for how we know other minds and predict others’ behavior.